Three new species and two new records of Echinothuriidae (Echinodermata: Echinothurioida) from seamounts in the Northwest Pacific Ocean: Diversity, phylogeny and biogeography of deep-sea echinothuriids - Zheng, Wanrui; Sun, Shao’e; Sha, Zhongli; Xiao, Ning (Frontiers in Marine Science, 2022)
The soft sea urchins Echinothuriidae Thomson, 1872, constitute the most commonly encountered sea urchins in the bathyal environment. The echinothuriids are common and frequently abundant in the Indo-Pacific, but the species diversity is still not completely known yet. Our examination of echinoid specimens collected from seven seamounts in the Northwest Pacific Ocean revealed three new species and two new records. The three new species are described as Araeosoma cucullatum sp. nov., Araeosoma polyporum sp. nov., and Hygrosoma involucrum sp. nov. The two new records included two species from the genus Araeosoma. They are distinguished from each other and from congeners by the following characteristics: coloring, ambulacrum, interambulacrum, apical system, spines, and pedicellariae. The identities of the five species are well supported by genetic distance and phylogenetic analyses based on the mitochondrial cytochrome oxidase subunit I (COI) and 16S rRNA genes. Based on the distribution data, we explored the distribution patterns of Araeosoma, Calveriosoma, Hapalosoma, Sperosoma, Tromikosoma, and Hygrosoma, the six echinothuriid genera occurring in deep sea, and delineated 10 isolated deep-sea biogeographic provinces all over the world. The Western Pacific harbors higher species diversity of deep-sea echinothuriids than other sea areas worldwide, indicating that the Western Pacific may play an important part in the dispersal and speciation of deep-sea echinothuriids.